The Influence of Competence and Motivation on Employee Job Satisfaction: A Study at the Pangalengan District Office, Bandung Regency - Nurhamdani, Dani; Siddiq, Andhika Mochamad (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
This study aims to examine the influence of competence and motivation on employee job satisfaction in a public sector setting, specifically at the Pangalengan District Office, Bandung Regency. Using a quantitative approach with saturated sampling, data were collected from 40 civil servants through questionnaires and analyzed using multiple linear regression. The findings reveal that work motivation has a significant and positive effect on job satisfaction, while competence shows no significant partial impact. The regression model is statistically significant, with competence and motivation together explaining 54.6% of the variation in job satisfaction. These results highlight the strategic role of motivation particularly intrinsic factors such as achievement, recognition, and affiliation in enhancing employee satisfaction. Meanwhile, the non-significant influence of competence suggests potential gaps in placement or skills alignment among personnel. The study underscores the importance of motivation-driven human resource strategies to improve satisfaction and performance in public organizations.